2019
DOI: 10.1002/ijc.32127
|View full text |Cite
|
Sign up to set email alerts
|

Germline BRCA2 K3326X and CHEK2 I157T mutations increase risk for sporadic pancreatic ductal adenocarcinoma

Abstract: Rare truncating BRCA2 K3326X (rs11571833) and pathogenic CHEK2 I157T (rs17879961) variants have previously been implicated in familial pancreatic ductal adenocarcinoma (PDAC), but not in sporadic cases. The effect of both mutations in important DNA repair genes on sporadic PDAC risk may shed light on the genetic architecture of this disease. Both mutations were genotyped in germline DNA from 2,935 sporadic PDAC cases and 5,626 control subjects within the PANcreatic Disease ReseArch (PANDoRA) consortium. Risk e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…rs17879961 (I157T), a likely causal[ 16 ] missense variant located in a CHEK2 functional domain that reduces or abolishes substrate binding[ 25 ], was previously reported to have opposite directions of effects on lung adenocarcinoma and lung squamous cell carcinoma and for lung cancer between smokers and non-smokers[ 26 , 27 ]. Moreover, the risk association of rs17879961 has been reported to vary across tissue locations/cell-types, as this variant has been associated with a higher risk of pancreatic ductal adenocarcinoma [ 28 ], chronic lymphocytic leukemia [ 29 ], and colorectal cancer [ 30 ], and also associated with a lower risk of aerodigestive squamous cell carcinoma [ 31 ] and ovarian cancer [ 32 ]. To our knowledge, rs67397200 and rs7072776 have not previously been shown to be associated with subtypes in opposite directions.…”
Section: Resultsmentioning
confidence: 99%
“…rs17879961 (I157T), a likely causal[ 16 ] missense variant located in a CHEK2 functional domain that reduces or abolishes substrate binding[ 25 ], was previously reported to have opposite directions of effects on lung adenocarcinoma and lung squamous cell carcinoma and for lung cancer between smokers and non-smokers[ 26 , 27 ]. Moreover, the risk association of rs17879961 has been reported to vary across tissue locations/cell-types, as this variant has been associated with a higher risk of pancreatic ductal adenocarcinoma [ 28 ], chronic lymphocytic leukemia [ 29 ], and colorectal cancer [ 30 ], and also associated with a lower risk of aerodigestive squamous cell carcinoma [ 31 ] and ovarian cancer [ 32 ]. To our knowledge, rs67397200 and rs7072776 have not previously been shown to be associated with subtypes in opposite directions.…”
Section: Resultsmentioning
confidence: 99%
“…An increased risk has been documented in patients with melanoma [ 242 ], endometrial [ 243 , 244 ], or testicular cancer [ 245 ]. An association with pancreatic cancer is less evident [ 20 , 246 , 247 , 248 , 249 ], but mutations in genes coding for DDR proteins (including CHEK2 ) in pancreatic cancer patients were associated with improved survival [ 250 , 251 , 252 , 253 ]. Germline CHEK2 variants were shown to protect against lung cancer, including in patients with a tobacco-related disease [ 134 , 254 ].…”
Section: Germline Chek2 Variantsmentioning
confidence: 99%
“…Several PDAC GWAS studies have been performed over the past decade [54][55][56][57][58][59] and have identified common variants associated with risk of pancreatic cancer in European populations (Figure 1). Obazee et al [60] used the PANDoRA dataset to validate a truncating BRCA2 k336X (rs11571833) and pathogenic CHEK2 I157T (rs17879961) variants. Both genes are critical in DNA repair and the maintenance of genomic stability.…”
Section: Inherited Predisposition Locimentioning
confidence: 99%